Evidence for e+e− →γχc1, 2 at center-of-mass energies from 4.009 to 4.360 GeV*Supported by National Key Basic Research Program of China (2015CB856700), Joint Funds of National Natural Science Foundation of China (11079008, 11179007, U1232201, U1332201, U1232107), National Natural Science Foundation of China (NSFC) (10935007, 11121092, 11125525, 11235011, 11322544, 11335008), Chinese Academy of Sciences (CAS) Large-Scale Scientific Facility Program, CAS (KJCX2-YW-N29, KJCX2-YW-N45), 100 Talents Program of CAS, INPAC and Shanghai Key Laboratory for Particle Physics and Cosmology; German Research Foundation DFG (Collaborative Research Center CRC-1044), Istituto Nazionale di Fisica Nucleare, Italy, Ministry of Development of Turkey (DPT2006K-120470), Russian Foundation for Basic Research (14-07-91152), U. S. Department of Energy (DE-FG02-04ER41291, DE-FG02-05ER41374, DE-FG02-94ER40823, DESC0010118), U.S. National Science Foundation, University of Groningen (RuG) and Helmholtzzentrum fuer Schwerionenforschung GmbH (GSI), Darmstadt, WCU Program of National Research Foundation of Korea (R32-2008-000-10155-0). (April 2015) - Ablikim 麦, M. 迪娜; Achasov, M. N.; Ai 艾, X. C. 小聪; Albayrak, O.; Albrecht, M.; Ambrose, D. J.; Amoroso, A.; An 安, F. F. 芬芬; An 安, Q. 琪; Bai 白, J. Z. 景芝; Ferroli, R. Baldini; Ban 班, Y. 勇; et al.
Abstract: Using data samples collected at center-of-mass energies of s = 4.009, 4.230, 4.260, and 4.360 GeV with the BESIII detector operating at the BEPCII collider, we perform a search for the process e + e − → γχc J ( J =0, 1, 2) and find evidence for e + e − → γχc1 and e + e − → γχc2 with statistical significances of 3.0σ and 3.4σ, respectively. The Born cross sections σ B (e + e − → γχc J ), as well as their upper limits at the 90% confidence level (C.L.) are determined at each center-of-mass energy.